PRODUCTION MASK SCUBA TYPE ON UMKM CAHAYA PRINTING - Yuyun Yuniar Rohmatin (Asosiasi Dosen Muda Indonesia, 2022)
Scuba mask is a type mask which made from a tight and elastic type of fabric that provides comfort when used. PT. Cahaya Digital Printing is one of companies engaged in digital printing that produces masks which are currently used by the public. The purpose of this study was to analyze production process of scuba masks from raw materials to mask products. The scuba mask production process uses scuba cloth as raw material which though a printing process on a digital printing machine which has a print area of up to 1.5 m with a print speed of up to 15 m2 per hour to print according design to customer requirement, manual press process to cut the mask to size and scuba printing and sewing and overlay processes using a sewing machine that has a stitch length of 0-5 mm and a sewing speed of up to 4500 s.p.m to sew the edges of the mask to make look neat and not stringy.